METODA PENGHILANGAN ZAT BESI DAN MANGAN DI DALAM PENYEDIAAN AIR MINUM DOMESTIK - Said, Nusa Idaman (Center for Environmental Technology, 2005)
Small amounts of iron and manganese are quite common in domestic water supply because of the presence of iron and manganese in the soil and rock formations through which the water passes in reaching the point of use. Iron and manganese is characterized by red-brown staining of bathroom fixtures and laundry, and cause taste and odor problems. Iron and manganese are brought into solution by biological reactions under anaerobic reducing conditions. When the water is exposed to air or oxygen, oxidation of iron and manganese occurs slowly, forming objectionable colloidal precipitates. The deposition of these precipitates will stain plumbing fixtures, interfere with laundering, and cause difficulties in water distribution systems by supporting growth of microorganisms such as clonotrix and crenotrix that can clog pipelines and cause taste and odor problems. Processes in which oxidation is followed by removal of suspended solids can effectively remove soluble iron and manganese from water. Three common processes for removing iron and manganese are: aeration-filtration, chlorination filtration, and potassium permanganate-manganese greensand filtration. This article describes these processes and present result from pilotÃ¢â‚¬â„¢s studies of iron and manganese removal from water.Ã‚Â Kata kunci : zat besi, mangan, aerasi, kkhlorinasi, filtrasi, mangan zeolit.